GAMBARAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL DI PUSKESMAS KALIGESING - Kurniawati, Nindya; Ayu Anjani, Siska (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
Antenatal care (ANC) examination is a pregnancy examination to optimize the mental and physical health of pregnant women so that they are able to face childbirth, the postpartum period, preparation for breastfeeding and the return to normal reproductive health (Manuaba, 2010). ANC visits at least 4 times consisting of K1/1st trimester (0-12 weeks) 1 time, 1 time in the second trimester and 2 times in the third trimester (Bartini, 2012). The majority of pregnant women at the Kaligesing Community Health Center (90%) complied with the minimum ANC visits and there were 2 respondents who did not meet the standards. This research aims to determine the description of the implementation of antenatal care for pregnant women in the third trimester at the Kaligesing Community Health Center. The research method is descriptive research type, the population of all pregnant women in the third trimester at the Kaligesing Community Health Center is 33 respondents, total sampling technique, research time October 2018- June 2019, percentage and central tendency formula analysis, MCH book measuring tool. The research results are based on the results of research on the coverage of antenatal care visits for pregnant women in the third trimester that meet the minimum visit standards, there are 31 (93.94%), while those that do not meet there are 2 (6.06%). Coverage of antenatal care visits for pregnant women in the third trimester at the Kaligesing Community Health Center in 2019 is according to standards. It is hoped that health workers will maintain and improve ANC services for third trimester pregnant women. Keywords: Antenatal Care